2020
DOI: 10.1002/chem.202003167
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐only Lewis Pairs of Rhodium with s, p and d‐Block Metals

Abstract: Metal‐only Lewis pairs (MOLPs) in which the two metal fragments are solely connected by a dative M→M bond represent privileged architectures to acquire fundamental understanding of bimetallic bonding. This has important implications in many catalytic processes or supramolecular systems that rely on synergistic effects between two metals. However, a systematic experimental/computational approach on a well‐defined class of compounds is lacking. Here we report a family of MOLPs constructed around the RhI precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 156 publications
1
18
0
Order By: Relevance
“…Thus their reactivity is predicted to mimic that of more traditional organometallic nucleophiles such as Cp*Rh(PMe 3 ) 2 . 29…”
Section: Resultsmentioning
confidence: 99%
“…Thus their reactivity is predicted to mimic that of more traditional organometallic nucleophiles such as Cp*Rh(PMe 3 ) 2 . 29…”
Section: Resultsmentioning
confidence: 99%
“…20 In addition, the Grignard reagent MeMgBr could be regarded as a metal Lewis acidic fragment that interacts with the metal Lewis base (η 5 -C 5 Me 5 )Rh(PMe 3 ) 2 16 to access metal-only Lewis pairs 17 (Scheme 6), which represent highly unusual examples containing unsupported Rh–Mg dative bonds. 21…”
Section: Synthesis Of Heterometallic Complexes Containing Mg- or Zn-m...mentioning
confidence: 99%
“…Later, Campos et al reported a series of heterobimetallic Zn–TM complexes, such as (bhq) 2 PdZn(C 6 F 5 ) 2 (bhq: cis -bis(1,10-benzo[ h ]quinolinato) 46a , (bhq) 2 PdZn(C 6 H 5 ) 2 46b , (η 5 -C 5 Me 5 )Rh(PMe 3 ) 2 ZnMe 2 47a , and (η 5 -C 5 Me 5 )Rh(PMe 3 ) 2 Zn(C 5 F 5 ) 2 47b (Scheme 15), from the reactions of different non-hydride transition metal complexes with dialkyl zinc compounds. 21,40 Recently, heterobimetallic Zn–Pt complexes, (Cy 3 P) 2 PtZnBr 2 48a and ( t Bu 3 P) 2 PtZn(C 6 F 5 ) 2 48b , bearing Pt–Zn dative bonds were synthesized through the reactions of Pt(PR 3 ) 2 (R = Cy, t Bu) with ZnBr 2 and Zn(C 6 F 5 ) 2 , respectively. 41…”
Section: Synthesis Of Heterometallic Complexes Containing Mg- or Zn-m...mentioning
confidence: 99%
“…Encouraged by this finding, we sought to apply this protocol to another transition metal. The rhodium(I) piano‐stool complex Rh(Cp*)(PMe 3 ) 2 is known to react as a metal‐centered Lewis base, [24] therefore we reasoned that it too would be an appropriate precursor to bridging cyaphido complexes. Heating a mixture of A and Rh(Cp*)(PMe 3 ) 2 at 80 °C overnight results in the liberation of trimethylphosphine (observed by 31 P{ 1 H} NMR spectroscopy), and the formation of the gold(I)/rhodium(I) bridging cyaphide complex Au(IDipp)(μ 2 −C≡P)Rh(Cp*)(PMe 3 ) ( 3 ; Scheme 2).…”
Section: Figurementioning
confidence: 99%